2021
DOI: 10.1136/bmjopen-2021-049752
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of asymptomatic COVID-19 cases among ascertained SARS-CoV-2 infections in different regions and population groups in 2020: a systematic review and meta-analysis including 130 123 infections from 241 studies

Abstract: IntroductionAsymptomatic infection of SARS-CoV-2 may lead to silent community transmission and compromise the COVID-19 pandemic control measures. We aimed to estimate the rate of asymptomatic COVID-19 from published studies and compare this rate among different regions and patient groups.MethodsIn this systematic review and meta-analysis, electronic databases including Medline, Embase, PubMed and three Chinese electronic databases (Chinese National Knowledge Infrastructure [CNKI], WanFang Data and China Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 35 publications
(31 reference statements)
2
36
2
Order By: Relevance
“…Estimates from meta-analysis might be precise, but are likely to be unreliable owing to unacceptably high levels of heterogeneity. In three large systematic reviews, overall estimates had narrow confidence intervals [14-16], but I 2 values were 94-99% and prediction intervals, which show the extent of all between-study variability were not reported [17]. The prediction intervals that we calculated extended more or less from zero to 100% (S2 Appendix), making differences in estimates between these studies hard to interpret.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Estimates from meta-analysis might be precise, but are likely to be unreliable owing to unacceptably high levels of heterogeneity. In three large systematic reviews, overall estimates had narrow confidence intervals [14-16], but I 2 values were 94-99% and prediction intervals, which show the extent of all between-study variability were not reported [17]. The prediction intervals that we calculated extended more or less from zero to 100% (S2 Appendix), making differences in estimates between these studies hard to interpret.…”
Section: Discussionmentioning
confidence: 91%
“…The number of published studies about SARS-CoV-2 is also increasing continuously and the types of published studies are also changing [10], including the designs of studies about asymptomatic infection. In systematic reviews of studies published to April 2021, reported point estimates from random effects meta-analysis models range from 17 to 41% [11][12][13][14][15][16]. Authors of these reviews typically report values of the I 2 statistic >90 [17,18], but heterogeneity is often not explored in detail and prediction intervals, which give information about sampling error and variability between studies, are recommended but rarely reported [17,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of specific comorbidities that increase the risk of developing severe COVID-19 [ 23 ], infection with SARS-CoV-2 can be relatively mild and even asymptomatic [ 24 ]. To date, one published trial has investigated the effects of vitamin C supplementation on SARS-CoV-2 symptoms [ 25 ].…”
Section: Attenuating Infection Symptoms and Severitymentioning
confidence: 99%